Pengelolaan Alokasi Dana Desa (ADD) Terhadap Pembangunan Gampong - Husin Amin (Journal of Social and Policy Issues, 2022)
This research aims to find out how the system of utilizing Village Fund Allocation (ADD) in the construction of facilities and infrastructure in Babul Makmur village of west Simeulue district. The location of this research is in Babul Makmur Village using descriptive research methods. The results showed that the use of Village Fund Allocation (ADD) in the construction of facilities and infrastructure starts from facilitating work and can be carried out properly, while utilization in increasing productivity is not affected. Furthermore, utilization by increasing effectiveness in the development of facilities and infrastructure can run and have an impact on the community because it can help the community improve its welfare. In addition, factors that affect activities are the absence of delays in disbursement of village funds and lack of public awareness of village development. The advice in this study is that the village government should increase socialization about the use of village funds and increase the commitment and consistency of the government and the community in order to carry out activities in the form of cooperation